2020
DOI: 10.1021/acsami.0c12330
|View full text |Cite
|
Sign up to set email alerts
|

Do New MOFs Perform Better for CO2 Capture and H2 Purification? Computational Screening of the Updated MOF Database

Abstract: High-throughput computational screening of metal organic frameworks (MOFs) enables the discovery of new promising materials for CO 2 capture and H 2 purification. The number of synthesized MOFs is increasing very rapidly, and computation-ready, experimental MOF databases are being updated. Screening the most recent MOF database is essential to identify the best performing materials among several thousands. In this work, we performed molecular simulations of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 62 publications
(121 reference statements)
1
53
0
1
Order By: Relevance
“…We recently performed high-throughput computational screening of 10,221 MOFs retrieved from the Cambridge Structural Database (CSD) 28 for CO 2 /H 2 separation and showed that MOFs perform well as CO 2 adsorbents. 29 In this work, we first utilized CSD ConQuest software 30 and conducted a connectivity search on these 10,221 MOFs. The guidelines described in the literature 27 were followed for targeted classification of MOFs, and 933 MOFs with Zn-oxide nodes were identified.…”
Section: Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently performed high-throughput computational screening of 10,221 MOFs retrieved from the Cambridge Structural Database (CSD) 28 for CO 2 /H 2 separation and showed that MOFs perform well as CO 2 adsorbents. 29 In this work, we first utilized CSD ConQuest software 30 and conducted a connectivity search on these 10,221 MOFs. The guidelines described in the literature 27 were followed for targeted classification of MOFs, and 933 MOFs with Zn-oxide nodes were identified.…”
Section: Computational Methodsmentioning
confidence: 99%
“… 25 We aimed to work on relatively simple MOF structures and eliminated the MOFs consisting of mixed linkers and/or functional groups due to the following reasons: (i) MOFs designed with mixed linker strategies can have defects, 31 , 32 or differing topologies and crystal structures, 33 but we aimed to work on MOFs with similar topologies after metal exchange and with a defect-free, homogeneous adsorption surface. (ii) MOFs with functional groups can have strong electrostatic interactions with CO 2 as shown in our previous works 29 , 34 but we aimed to isolate the influence of metal exchange on CO 2 /H 2 and CO 2 /CH 4 selectivity by omitting the MOFs with functional groups and mixed linkers. 769 MOFs with Zn-oxide nodes, a single type of linker, and no functional groups were divided into two final subgroups depending on the shape of the metal cluster (coordination of the node): 140 IRMOF-like MOFs (IRMOFs) and remaining (629) MOFs with Zn-oxide nodes (ZnO-MOFs).…”
Section: Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a wide range of chemical environments and high porosities of MOFs, gas permeability and membrane selectivity of MOFs have been reported in a very large range. [97][98][99] In addition, when molecular sieving mechanism is used to assess the gas separation performances of MOF, extremely high membrane selectivities (up to 10 8 ) are reported in the literature. 72 For these reasons, it is difficult to observe a trade-off or define the upper-performance limits of MOF membranes.…”
Section: Simulated Membrane Properties Of Mofsmentioning
confidence: 99%
“…Inspired by the advancements mentioned above and by the vast available literature on UiO‐66 MOF as illustrated in Figure 3, the current review, therefore, focuses on UiO‐66 MOFs for CO 2 capture, separation and conversion applications. Although there are numerous papers and reviews covering MOFs applied to CO 2 capture, separation, and conversion [15,71–80] . However, this review′s importance lies particularly in the versatility of the pristine, functionalized and composites of UiO‐66 MOFs materials covering the literature from 2008 to 2020.…”
Section: Introductionmentioning
confidence: 99%